PENANGANAN MASALAH OVERKAPASITAS TERHADAP NARAPIDANA LANJUT USIA DI LEMBAGA PEMASYARAKATAN - Taqiyuddin, Zaki Difa; Subroto, Mitro (Universitas Nusa Cendana, 2024)
Overcapacity in prisons often occurs among the elderly from 2019 to 2022. This research aims to address the problem of overcapacity for elderly prisoners in correctional institutions. The method in this research uses a qualitative approach through literature studies. The results of the research show that the overcapacity that occurs every year has increased in prison residents. It is known that prisoners increase every year. The causes of prison overcapacity are pre-trial detention, criminal sanctions policies for drug cases, and lack of access for convicts to advocates and others. An elderly person still has the rights and obligations of an Indonesian citizen. The aspects that play a role are health and medical care, mental welfare, special treatment, judicial processes, rehabilitation and care, and legal protection. The legal system considers the special needs of elderly prisoners, for example in terms of health, mental well-being, and human rights. One way is restorative justice where imprisonment is not only a means of punishment but also a place for training law violators in Indonesia. Keywords: Elderly; Prisoner; Overcapacity